Self-excited flow oscillation in an abruptly expanding circular duct as the noise source - SZUMOWSKI, Andrzej P.; PIECHNA, Janusz (Archives of Acoustics, 1983)
The behaviour of oscillations in subsonic flow in a duct with a sudden enlargement of cross-section has been investigated experimentally. The mechanism of one type of oscillation has been found and explained. In this type of oscillation the resonant oscillation of a gas column in the part of a duct with constant cross-section is sustained by flow in the extended part of the duct. The flow is accompanied by periodically occurring and downstream moving annular vortices which close the feedback loop. The shadow graph visualization has confirmed the existence of this coherent vortex structure in the flow.